2022
DOI: 10.2166/ws.2022.130
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of land-use/land-cover changes on nutrient losses in agricultural catchment, southern Ethiopia

Abstract: Assessing the impact of land-use/land-cover (LULC) change and nutrient loads on water systems is a key issue, where different water uses raise water quality concerns. This study aimed to enumerate the extent of the LULC change from 1986 to 2018, its measurable impacts on nutrient losses and major pollution areas based on the SWAT in the Bilate catchment, Southern Ethiopia. The sequential uncertainty fitting version two (SUFI-2) algorithm in SWAT-CUP was used in calibration and validation. Calibration and valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
0
2
0
1
Order By: Relevance
“…Tong et al ( 2019 ) observed substantial soil organic carbon and TN losses when woodland and grassland were converted to cultivated land types. Similarly, Kooch and Noghre ( 2020 ) demonstrated due to variations in soil organic matter while in the tropics, Kuma et al ( 2022 ) showed high rates of nutrient loss in agricultural catchments. These findings collectively reveal that land cover plays a crucial role in nutrient cycling but, as shown in our study, delineation to individual subcatchment or stream scale may be required to identify causal relationships.…”
Section: Discussionmentioning
confidence: 91%
“…Tong et al ( 2019 ) observed substantial soil organic carbon and TN losses when woodland and grassland were converted to cultivated land types. Similarly, Kooch and Noghre ( 2020 ) demonstrated due to variations in soil organic matter while in the tropics, Kuma et al ( 2022 ) showed high rates of nutrient loss in agricultural catchments. These findings collectively reveal that land cover plays a crucial role in nutrient cycling but, as shown in our study, delineation to individual subcatchment or stream scale may be required to identify causal relationships.…”
Section: Discussionmentioning
confidence: 91%
“…Kajian terkait perubahan penggunaan lahan sudah banyak dilakukan oleh peneliti terdahulu baik kajian yang berupa perubahan penggunaan lahan seperti yang dilakukan oleh Chen et al, (2019); Kuma et al, (2022); Manikandan & Rangarajan, (2023); dan Siddik et al, (2022) ataupun kajian terkait kesesuaian penggunaan lahan permukiman seperti yang dilakukan oleh Li et al, (2022); Litasari et al, (2022); Nurzakiah et al, (2022); dan Utami et al, (2021). Pada kajian perubahan penggunaan lahan, penelitian-penelitian tersebut mengkaji perubahan penggunaan lahan berdasarkan beberapa temporal data dengan tujuan memperlihatkan gambaran perubahan penggunaan lahan secara keseluruhan dan dampak yang terjadi terhadap lingkungan yang ada di lokasi penelitian.…”
Section: Pendahuluanunclassified
“…Beside was resulting water path contamination, it is highly related as one of main cause of food insecurity for many developing countries because of gap in agricultural production (Anas et al, 2020;Dinnes et al, 2002;Kimbi et al, 2022;Okamoto et al, 2021) due to poor trend in cropland nitrogen fertilizer management. Changes in the climate in the Bilate watershed have been recognized in previous research as a climatic impact for nitrogen fertilizer loss on agricultural land however taking the whole watershed was agricultural land; it has still highlighted a knowledge gap in its research without crop types and cropping season (Kuma et al, 2022). Since agricultural land nitrogen loss is not continuous, it is important to consider specific cropping season, crop classification and biomass index (Cao et al, 2014;Dinnes et al, 2002;Elrashidi et al, 2005; Z. H. Wang & Li, 2019) crop land nitrogen loss parameters, such as main cropping season and pattern of crop growth has to be calibrated for (NO -3-N) runoff\leaching analysis.…”
Section: Introductionmentioning
confidence: 99%